Percepción de la identidad organizacional en trabajadores administrativos de una universidad pública - Orellana Méndez, Gaspar (2023)
This research aims to adapt the Organizational Identity Scale of Orellana et al. (2011) and diagnose the perception of Organizational Identity in 66 administrative workers of a public university. The scale was adapted for this population with an empirical validity subtest-test (Pearson's r Corrected greater than .20) and moderate reliability with Cronbach's alpha ( .65). It was found that the perception of Organizational Identity is neutral and only in the corporate dimension was it favorable. Males, older adults, and those named are those who perceive the Organizational Identity of the university the best. This requires an emphasis on involving the organization to the hired managers and stimulating the dimensions of Personal and Social Identity